The Venture Bros. Season two [videorecording (DVD)] - McCulloch, Chris; Urbaniak, James, 1963-; Sinterniklaas, Michael (Distributed by Warner Home Video, 2007)
An inspired spoof of 1960s action cartoons such as Jonny Quest, The Venture Bros. follows the bizarre misadventures of Hank and Dean, who believe themselves to be an unusually gifted team of brains and braun while really having little of either.